Information, Communication and Mass Media; A Positive Outlook - Parajuli, Pradip (Historical Journal, 2020)
Mass media was gifted on the Nepali soil early as one and half century ago. We have no longer history on mass media and journalism as other countries compared to the four and half century long history of world journalism, the history of Nepalese mass media and journalism is undoubtedly a recent phenomenon. The art and science of using information to one's advantage is one of the keys to influence and power in any society. As a matter of fact man alone has the capacity to generate information through new symbols, and to share the meaning of these symbols with fellow men. One may even look with advantage at human history through the information/ communication prism. It is the history of an ever-increasing capability to create new generated information and shares it with others to their mutual advantage to ward off danger, to inform about the new opportunities, etc. In brief, information/ communication are the key to organized human life.